2008
DOI: 10.1289/ehp.10861
|View full text |Cite
|
Sign up to set email alerts
|

Drinking-Water Arsenic Exposure Modulates Gene Expression in Human Lymphocytes from a U.S. Population

Abstract: BackgroundArsenic exposure impairs development and can lead to cancer, cardiovascular disease, and diabetes. The mechanism underlying these effects remains unknown. Primarily because of geologic sources of contamination, drinking-water arsenic levels are above the current recommended maximum contaminant level of 10 μg/L in the northeastern, western, and north central regions of the United States.ObjectivesWe investigated the effects of arsenic exposure, defined by internal biomarkers at levels relevant to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 62 publications
9
84
1
Order By: Relevance
“…Supplementation of spirulina to arsenic-treated goats did not significantly modify the IgG-positive to IgG-negative lymphocyte ratio or the IgM-positive lymphocytes in the lymph node. Arsenic has been recognized as a powerful immunomodulatory agent in many laboratory animals and in epidemiological studies (18). However, the insignificant effect of spirulina on immune functions in the present study might be due, in part, to large intake of green grass, which might provide more micronutrients and antioxidants than the small amount of spirulina.…”
Section: Discussioncontrasting
confidence: 56%
“…Supplementation of spirulina to arsenic-treated goats did not significantly modify the IgG-positive to IgG-negative lymphocyte ratio or the IgM-positive lymphocytes in the lymph node. Arsenic has been recognized as a powerful immunomodulatory agent in many laboratory animals and in epidemiological studies (18). However, the insignificant effect of spirulina on immune functions in the present study might be due, in part, to large intake of green grass, which might provide more micronutrients and antioxidants than the small amount of spirulina.…”
Section: Discussioncontrasting
confidence: 56%
“…These studies have the potential to yield important insights about mechanisms of carcinogenesis. For example, Russo et al (9) reported a genomic signature associated with parity status in histologically normal breast tissue and Andrew et al (10) presented a lymphocyte gene expression signature associated with high versus low exposure to drinking water arsenic. Webb et al (2007) identified several challenges and limitations associated with matching and restriction for confounding control in microarray analyses, but an approach that has received surprisingly little attention is application of statistical methods.…”
Section: Causal Contrasts and Genomic Data: Controlling Confounding Amentioning
confidence: 99%
“…Exposure to a carcinogenic metal, such as arsenic, has been associated with altered gene expression patterns both in vitro and in vivo, and it has been demonstrated that the arsenicinduced changes in gene expression may be epigenetically regulated (2)(3)(4)(5)(6)(7)(8)(9). Although arsenic is capable of inducing changes in gene expression by altering the levels of post-translational histone modifications in the promoters of genes, alterations in the expression of the histone genes themselves by arsenic has not been studied.…”
mentioning
confidence: 99%